Equalising power imbalances or a trail of broken promises? A qualitative study on engaging people with diverse lived experience of marginalisation in food policymaking in Australia - Carolina Venegas Hargous; Kevin Kapeke; Kathryn Backholer; Dheepa Jeyapalan; Veronica Nunez; Jennifer Browne; Anna Peeters; Alexandra Chung; Steven Allender; Victoria Stead; Yin Paradies; Christina Zorbas (BMC Public Health)
Abstract Background Achieving nutrition and health equity warrants understanding lived experiences of marginalisation. Yet, people with diverse lived experiences are often inadequately included in food policy advocacy, agenda setting, and development. We aimed to explore cross-sectoral perceptions of engaging people with lived experiences of marginalisation in food policymaking in Australia, specifically in terms of challenges, enablers, required actions, and potential outcomes of doing so. Methods In-depth semi-structured interviews were conducted with 24 people with expertise in food policy and/or community engagement from academic, government, advocacy, and community sectors. Interviews were inductively and deductively coded using the Knowledge-to-Action framework. Results Participants identified few food policymaking examples where people with lived experience have been meaningfully engaged. Reported barriers included the lack of time, resources, and prioritisation across sectors and the lack of political commitment to inclusive policymaking. Having access to successful examples, existing networks of actors and flexible funding were among the few enablers identified. Several actions were deemed necessary to effectively engage people with lived experience in food policymaking and improve current practice: (1) having a dedicated budget; (2) enabling true collaboration where people with lived experience are valued, effectively engaged, sufficiently represented, have the opportunity to work alongside decision-makers, and where power is equalised; (3) striving to do no harm to the people engaged; and (4) ensuring results from engaging people with lived experience are effectively disseminated. Conclusions We provide a list of practical recommendations to guide more inclusive, equitable and fit-for-purpose food policymaking into the future. These recommendations seek to challenge dominant systems of discrimination by demonstrating how we can tangibly shift to ways of working that value and elevate the power of people who are often excluded from many decision-making systems, specifically when it comes to food and nutrition.